Chief Executive Officer Dismissal: A Multidisciplinary Integration and Critical Analysis. Issue 2 (April 2021) - Berns, John P.; Gupta, Vishal K.; Schnatterly, Karen A.; Steele, Clarissa R.
Dismissal (or involuntary exit) of the chief executive officer (CEO) is a significant milestone with substantial implications for organizations and their members. The growing occurrence of CEO dismissals, and increased academic interest in this area, motivates our comprehensive multidisciplinary synthesis of the extant literature. Our analysis is organized around understanding the antecedents and outcomes of CEO dismissal, and the relevant moderators that play a contingent role in the nomological network. Based on our synthesis of the extant cross-disciplinary literature, we offer a multilevel organizing framework articulating the current state of research on CEO dismissal. In doing so, we catalog and analyze the concepts, theories, and constructs prevalent in the CEO dismissal literature. We also offer an in-depth discussion for the field going forward and identify a constructive agenda for future research on CEO dismissal.